Dynamic spinal posture and pelvic position analysis using a rasterstereographic device - Michalik, Roman; Hamm, Juliane; Quack, Valentin; Eschweiler, Joerg; Gatz, Matthias; Betsch, Marcel (Journal of Orthopaedic Surgery and Research, 2020)
Background: Until recently, rasterstereographic analysis of the spine was limited to static measurements. However, understanding and evaluating the motion of the spine under dynamic conditions is an important factor in the diagnosis and treatment of spinal pathologies. The aim of this study was to study the spinal posture and pelvic position under dynamic conditions and compare it to static measurements using a dynamic rasterstereographic system. Methods: A total of 121 healthy volunteers (56 females; 65 males) were included in this observational study. The parameters trunk inclination, trunk imbalance, pelvic obliquity, kyphotic angle, lordotic angle, surface rotation, and lateral deviation were studied and compared under static and dynamic (1, 2, 4, 5 km/h) conditions using the system "Formetric 4D Motion®"(DIERS International GmbH, Germany). Results: Female volunteers had a higher lordotic angle than males under static conditions (p < 0.001). Trunk inclination (5.31° vs. 6.74°), vertebral kyphotic angle (42.53° vs. 39, 59°), and surface rotation (3.35° vs. 3.81°) increase under dynamic conditions (p < 0.001). Trunk inclination and lordotic angle both show significant changes during walking compared to static conditions (p < 0.001). Conclusion: The spinal posture differs between females and males during standing and during walking. Rasterstereography is a valuable tool for the dynamic evaluation of spinal posture and pelvic position, which can also be used to quantify motion in the spine and therefore it has the potential to improve the understanding and treatment of spinal pathologies. Trial registration: Retrospectively registered
CRIS-Team Scopus Importer:2022-07-20
Keywords: Dynamic; Gait posture; Rasterstereography; Spine; Surface topography